2014
DOI: 10.1186/1471-2474-15-116
|View full text |Cite
|
Sign up to set email alerts
|

The effect of perinatal brachial plexus lesion on upper limb development

Abstract: BackgroundDeficiency in upper limb development is a sequel of the perinatal brachial plexus palsy. The purpose of this study was to evaluate the effect of brachial plexus birth lesion on upper limb development.MethodsForty-four patients with unilateral obstetric brachial plexus palsy underwent measurements of both upper extremities. The average age at the time of evaluation was 6.8 years. Active motion was assessed using Gilbert-Raimondi, the modified MRC, and Al-Qattan scales. Paired t test was used for stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Horner's syndrome is evident on initial examination and characterized ptosis, miosis, and anhidrosis. Functionally, patients with permanent neurologic injury have been found to have slightly smaller dimensions of the affected limb, along with delayed skeletal maturation [17,18]. These children can expect the affected limb to be approximately 95 % the length and girth of the contralateral limb [19].…”
Section: Natural Historymentioning
confidence: 99%
“…Horner's syndrome is evident on initial examination and characterized ptosis, miosis, and anhidrosis. Functionally, patients with permanent neurologic injury have been found to have slightly smaller dimensions of the affected limb, along with delayed skeletal maturation [17,18]. These children can expect the affected limb to be approximately 95 % the length and girth of the contralateral limb [19].…”
Section: Natural Historymentioning
confidence: 99%
“…and 95% of the length of the contralateral limb at the final follow-up ranging from 12 to 16 years post FFGT. We compared the limb length differences of our patients with the literature data in the obstetric BPP treated without the FFGT (Bain et al, 2012;Gosk et al, 2014; Terzis and Kokkalis, 2010) and we did not detect any difference, although we recognize that the groups were not matched in terms of aetiology and severity of the palsy (the control group consisted of patients with birth-related palsy mostly limited to upper roots). Although our small sample precludes us from making any firm conclusions, we have no reason to believe that the FFGT further aggravates the already-disturbed growth of the paralysed extremity.…”
Section: Discussionmentioning
confidence: 89%
“…In this study report of 17 OBPI children, 6 had BTL surgery to improve their limb length 3 years after triangle tilt surgery. Gosk et al 30 reported the discrepancy of affected limb length and circumference and functional efficiency in 44 OBPI children in comparison with their unaffected limb. We recently demonstrated that elbow flexion and arm length were greatly improved in OBPI patients, who undergone BTL surgery.…”
Section: Discussionmentioning
confidence: 99%
“…1929 However, only a few publications with results over 10-year postoperative follow-up exist. 3034 Kirjavainen et al 34 reported their long-term postoperative follow-up results from a nationwide study with various soft tissue and bone surgeries performed by many surgeons in brachial plexus birth palsy patients (5–13 years follow-up). These authors (Kirjavainen et al 32 ) also reported later, their 12 years follow-up study results in 102 OBPI patients.…”
Section: Discussionmentioning
confidence: 99%